2021
DOI: 10.1039/d1cc02112e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in acyl radical enabled reactions between aldehydes and alkenes

Abstract: Radical-mediated functionalization of alkenes has been emerging as an elegant and straightforward protocol to increase molecule complexity. Moreover, the abstraction of a hydrogen atom from aldehydes to afford acyl radicals...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 112 publications
2
21
0
Order By: Relevance
“…In the reactions of these aliphatic aldehydes, although replacing the solvent with acetonitrile and raising the reaction temperature to 100 °C improved the yield of the products ( 3as – 3aw ), it was found that it was difficult for the reaction to completely consume 1a even with a prolonged reaction time. Compared with aryl aldehydes, the formation of aliphatic acyl radicals via alkyl aldehyde C­(sp 2 )–H bond cleavage remains relatively rare and challenging . Additionally, the aliphatic acyl radicals generated by the oxidation of aliphatic aldehydes under heated conditions can undergo sequent decarbonylation to form alkyl radicals, a process by which a range of alkylation reactions have been well utilized. , These may be the important reasons for the difficulty and low yields of aliphatic aldehydes in the present dearomatization.…”
Section: Results and Disscussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In the reactions of these aliphatic aldehydes, although replacing the solvent with acetonitrile and raising the reaction temperature to 100 °C improved the yield of the products ( 3as – 3aw ), it was found that it was difficult for the reaction to completely consume 1a even with a prolonged reaction time. Compared with aryl aldehydes, the formation of aliphatic acyl radicals via alkyl aldehyde C­(sp 2 )–H bond cleavage remains relatively rare and challenging . Additionally, the aliphatic acyl radicals generated by the oxidation of aliphatic aldehydes under heated conditions can undergo sequent decarbonylation to form alkyl radicals, a process by which a range of alkylation reactions have been well utilized. , These may be the important reasons for the difficulty and low yields of aliphatic aldehydes in the present dearomatization.…”
Section: Results and Disscussionmentioning
confidence: 66%
“…Compared with aryl aldehydes, the formation of aliphatic acyl radicals via alkyl aldehyde C(sp 2 )−H bond cleavage remains relatively rare and challenging. 18 Additionally, the aliphatic acyl radicals generated by the oxidation of aliphatic aldehydes under heated conditions can undergo sequent decarbonylation to form alkyl radicals, a process by which a range of alkylation reactions have been well utilized. 19,20 These may be the important reasons for the difficulty and low yields of aliphatic aldehydes in the present dearomatization.…”
Section: ■ Results and Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 b Through radical addition to the unsaturated bond to form a C–C bond, acyl radicals have been utilized in preparing diverse carbonyl compounds. 2 However, radical-coupling reactions between acyl and other carbon-centered radicals are rare. N-Heterocyclic carbene (NHC) catalysis has emerged as an attractive strategy in synthetic chemistry to access value-added organics via the formation of the key Breslow intermediate (BI).…”
Section: Introductionmentioning
confidence: 99%